Guidelines for Problem Solving about Verification of Unregistered Persons’ Legal Status and Rights in Rong Kho Sub-district, Wang Nuea District, Lampang Province - Channew, Maneerat; Chumphonwong, Tapanee (Rajapark Journal, 2022)
This research aimed to study the way to manage the problem of identifying the status and rights of persons under the local area of Rong Khor Subdistrict, Wang Nuea District, Lampang Province. This was qualitative research using data collection methods such as open-ended questionnaires and interviews with government officials. Data analysis was performed using content analysis techniques. As a result, it was found that there was a total of 97 people. Out of these groups, seven people have obtained Thai nationality, a group of people who only have registered status, but the other 12 Thai nationalities have not yet been certified, and there were groups of people who did not have registered status and have not yet received Thai nationalities for 78 persons. There were many problems related to proving the status and rights of legal persons, namely, the issue of evidence in proving birth that the applicants could not present to government officials, interlingual communication problems between applicants and government officials that cause miscommunication, knowledge problems regarding the applicant’s right to Thai nationality, problems with the provisions by law that authorize the chief of the district or provincial governor, as the case may be, to approve the request, and the problems of government officials who frequently change or relocate their positions as well as the fear of making mistakes.